PEMBELAJARAN DIFERENSIASI PADA ERA PENDIDIKAN MODERN (TINJAUAN ILMIAH TERHADAP KISAH BHAGAWAN DOMYA) (Adi Widya: Jurnal Pendidikan Dasar, 2024)
Modern education has evolved into the concept of "Merdeka Belajar", which gives students greater control over their education. In this context, differentiated learning, which recognizes the diversity of students and adjusts teaching to individual needs, becomes crucial. This article uses the story of Bhagawan Domya and his three students as a case study to explore the role of differentiated learning in meeting diverse learning needs in the modern education era. The story illustrates how Bhagawan Domya indirectly conducts in-depth assessments related to his students' learning needs. Differentiated learning involves adjusting content, processes, and products to support student development. In the era of "Merdeka Belajar", the combination of the freedom to learn the concept and differentiated learning creates an inclusive, motivating, and meaningful learning environment, enabling every student to reach their full potential.